Crowding out in an indefinitely repeated Asymmetric Trust Game - T. Dirkmaat; Stephanie Rosenkranz; V.W. Buskens (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2006)
In this paper we introduce an alternative version of the trust game by Dasgupta (1988) and Kreps (1990) that allows for asymmetric information. We use this version to study the effect of checking on the trustee's behaviour, checking is a control option the trustor can decide to use and that takes place after both trustor and trustee made their initial decisions. 'Checking' differs in this respect from the often in the literature found 'monitoring' that allows the trustor to control the trustee's behaviour before the trustee makes his decision. The game theoretical analysis suggests that checking increases cooperation. The experimental results show that this is only true for the selfish part of the trustee population. Honest trustee react negatively to checking, which is more in line with crowding out theory.
Keywords: 330; Trust; Asymmetric Information; Experiment; Checking; Crowding Out